PENGARUH PEMANFAATAN MEDIA INTERNET TERHADAP HASIL PEMBELAJARAN DESAIN BUSANA SISWA SMK - Widya Rahma Wati; Endang Wani Karyaningsih (UNIVERSITAS SARJANAWIYATA TAMANSISWA, 2017)
This study aimed to describe the influence of the use of internet toward learning achievement of fashion design, the use of internet, andÂ learning achievement of fashion design. This study was ex-post, facto.Student research subjects SMK N 4 Yogyakarta. Data colleting methods used questionnaires and documentation. Data analyzing methods used descriptive analysis and hypothesis testing by using Product Moment that was started by normality and linearity test.Â This study shows that the use of internet was in enough category with the percentage 64.29% and learning achievement of fashion design was in high category with relative frequency 62.86%. Based on the result of Product Moment, the score of rxy was 0,518. The score of r table in the significant level 5% for total respondents 70 was 0.235 (rxy 0,518 > r table 0,235). It could be stated there was a positive and significant influence of the use of internet toward learning achievement of fashion design. The determinant coefficient (R2) was 0.268, it means that the use of internet gave contribution for about 26.8%, while 73.2% was influenced by other factors Â Key words: the use of internet, learning achievement of fashion design.